Peran Teknologi Informasi dalam Membentuk Kewirausahaan Modern: Kajian Sistem Literatur Review Berbasis PRISMA - Dila, Rahmah; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The rapid development of Information Technology (IT) has had a significant impact on the modern entrepreneurial landscape. Technology is a major driver in creating new business opportunities, facilitating operational efficiency, and expanding market reach digitally. This study aims to systematically review the literature discussing the role of IT in the development of modern entrepreneurship using the Systematic Literature Review (SLR) method based on the Prisma (Preferred Reporting Items For Systematic Reviews and Meta-Analyses) guidelines. This study analyzed 100 scientific articles published between 2021-2025 and obtained from reputable databases such as Google Scholar, IEEE Xplore, and ScienceDirect. The results of the study show that IT plays a role in several important aspects, namely the development of digital business models, increasing managerial efficiency, utilizing e-commerce platforms, and supporting product and service innovation. In addition to its benefits, challenges were also found such as limited access to technology, lack of digital literacy, and dependence on IT infrastructure. These findings are expected to provide theoretical and practical contributions in the development of entrepreneurship that is adaptive to technological developments in the digital era